The Influence of Transformational Leadership Style on Village Apparatus Performance Through Work Motivation in East Halmahera Regency - Rian Pratama Abdi Mohamad; Adnan Rajak; Abdul Rahman Jannang (Jurnal Economic Resource, 2022)
This study aims to analyze the effect of a transformational leadership style on the performance of village officials through work motivation in East Halmahera Regency. The type of research used in this research is quantitative research. The sample selected was comprised of 90 village officials using a purposive sampling technique. Data was collected using a questionnaire and then analyzed using path analysis with the help of SPSS Version 26. The results of this study found that        1) Transformational leadership had a positive and significant impact on village officials' performance, 2) Transformational leadership had a significant and positive impact on work motivation, 3) Work motivation has a positive and significant impact on the Village Apparatus' performance, and 4) Indirectly, transformational leadership has a positive and significant effect on the performance of the Village Apparatus through work motivation in East Halmahera Regency.